2019
DOI: 10.1177/1129729818820200
|View full text |Cite
|
Sign up to set email alerts
|

Implications for maintaining vascular access device patency and performance: Application of science to practice

Abstract: Introduction:Vascular access devices are commonly inserted devices that facilitate the administration of fluids and drugs, as well as blood sampling. Despite their common use in clinical settings, these devices are prone to occlusion and failure, requiring replacement and exposing the patient to ongoing discomfort/pain, local vessel inflammation and risk of infection. A range of insertion and maintenance strategies are employed to optimize device performance; however, the evidence base for many of these mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 90 publications
1
14
0
Order By: Relevance
“…The incidence of adverse events in the control group was 61.2%, which was higher than 21.2% in the observation group. The conclusion showed that the clinical nursing path based on evidence-based medicine plays a better role in preventing venous thrombosis and adverse complications in long-term bedridden patients compared with the conventional nursing model [ 29 ]. Compared with the conventional nursing mode, personalized health education for patients could better improve the compliance of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of adverse events in the control group was 61.2%, which was higher than 21.2% in the observation group. The conclusion showed that the clinical nursing path based on evidence-based medicine plays a better role in preventing venous thrombosis and adverse complications in long-term bedridden patients compared with the conventional nursing model [ 29 ]. Compared with the conventional nursing mode, personalized health education for patients could better improve the compliance of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their common use in clinical settings, these devices are prone to occlusion and failure, requiring replacement and exposing the patient to ongoing discomfort/ pain, local vessel inflammation and risk of infection. [1][2][3]23] In order to prevent these complications, observation of the catheter area by nurses is very important, especially in irritant drug infusions. [20] However, it was seen that studies conducted on catheter vein duration and frequency of interventions especially in children are in a limited number in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It is an important issue for healthcare professionals to take measures against repeated invasive procedures and to increase such studies. [12,18,23] Jeong et al (2017) determined that the mean PIVC dwell time was 55.62±27 hours, mostly at 24-72 hours intervals, in 1596 pediatric patients. [20] In another study conducted on children who were between the ages 3-18, it was found that the mean duration of catheterization was 83.53 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should keep in mind that higher frequency and volume of flushing has been observed to have more peripheral IV complications, such as vessel damage, infection, and thrombosis. 19,20 Highpressure and high-volume injections should only be undertaken in emergency situations where there is no other alternative.…”
Section: Variablesmentioning
confidence: 99%